The Impact of Educational Digital Transformation Policies on Teachers’ Competencies in Indonesia - Gufron, Muhammad; Syahbani, Abdul Muis; Krik, Peter (Lembaga Publikasi Ilmiah Nusantara, 2026)
Educational digital transformation has become a central policy agenda in Indonesia as part of broader efforts to improve educational quality, equity, and system resilience in the digital era. This study examines the impact of educational digital transformation policies on teachers’ competencies in Indonesia, focusing on four interrelated dimensions: technological, pedagogical, professional, and social competencies. Employing a quantitative research design, data were collected through a structured questionnaire administered to primary and secondary school teachers across diverse regional contexts. Descriptive statistics and regression analysis were used to examine the extent to which policy implementation predicts variations in teachers’ competencies. The findings indicate that educational digital transformation policies have a significant and positive effect on teachers’ overall competencies. Technological competence emerges as the most strongly influenced dimension, reflecting the effectiveness of policy-driven provision of digital infrastructure, platforms, and systems in enhancing teachers’ operational digital skills. Pedagogical competence is also positively affected, suggesting that digital policies encourage the integration of technology into instructional planning, delivery, and assessment. However, the effects on professional and social competencies are comparatively weaker, highlighting that sustained professional development, supportive school leadership, and collaborative school cultures are critical mediating factors in translating policy into deeper professional growth. This study contributes to the literature on educational policy and digital transformation by providing empirical evidence from the Indonesian context, characterized by significant regional and institutional disparities. The findings underscore that digital transformation policies are most effective when implemented as part of a holistic reform strategy that integrates technological provision with continuous professional development, pedagogical support, and equity-oriented interventions. Practically, the study offers evidence-based implications for policymakers and school leaders seeking to design digital transformation policies that empower teachers as reflective professionals and promote sustainable improvement in teaching quality.